2020
DOI: 10.1155/2020/5292356
|View full text |Cite
|
Sign up to set email alerts
|

A Sociocultural Perspective on Second Language Writing: The Effect of Symmetrical versus Asymmetrical Scaffolding on Intermediate EFL Learners’ Writing Accuracy, Fluency, and Complexity and Their Attitudes

Abstract: This study investigated the effect of different patterns of scaffolding (symmetrical and asymmetrical) on Iranian English as a Foreign Language (EFL) students’ writing accuracy, fluency, and complexity. For this purpose, 90 intermediate female EFL learners took a Preliminary English Test (PET), based on which those whose scores fell one standard deviation below the mean were considered as low intermediate and those whose score was one standard deviation above the mean were considered as high intermediate learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The findings of the ANCOVA test showed that prior oral lexical knowledge in English was a strong predictor of students' success in the vocabularyenhancing intervention and that scaffolding was effective in helping students acquire vocabulary. Mohammadzadeh et al (2020) conducted different research to investigate the impact of symmetric scaffolding on upper-mediate learners' reading perception. Twenty intermediate EFL students took part in this investigation.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the ANCOVA test showed that prior oral lexical knowledge in English was a strong predictor of students' success in the vocabularyenhancing intervention and that scaffolding was effective in helping students acquire vocabulary. Mohammadzadeh et al (2020) conducted different research to investigate the impact of symmetric scaffolding on upper-mediate learners' reading perception. Twenty intermediate EFL students took part in this investigation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Mohammadzadeh et al (2020) conducted different research to investigate the impact of symmetric scaffolding on upper-mediate learners’ reading perception. Twenty intermediate EFL students took part in this investigation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to Ler (2012), rural cultural factors adversely affect English Proficiency. Numerous research indicates English as a second language would affect English writing proficiency in terms of accuracy, complexity, and fluency of writing (such as Mohammadzadeh et al, 2020;Saadat and Alavi, 2018;Vyatkina, 2012).…”
Section: Theoretical Perspectivementioning
confidence: 99%